PEMBELAJARAN BIPA DI INSTITUT PERTANIAN BOGOR: MOTIVASI, SIKAP, DAN HARAPAN MAHASISWA - nfn Krishandini; Endang Sri Wahyuni (Metalingua: Jurnal Penelitian Bahasa, 2016)
THE Indonesian language can be a requirement for all foreigners who will stayin Indonesia. Therefore, Bogor Agricultural University (IPB) offers BIPA coursesfor IPB students who will learn at the level of S1 and S2. However, the learnerswho attend BIPA IPB courses are dominated by IPB students who have to takea one-semester course before attending their class. This is because college classesare more likely to use Indonesian than any other language. In this study, thefollowing questions were investigated:1) What are the real motivations of foreignstudents who take BIPA , 2). What are their attitudes towards BIPA learning? and3) What are their expectations after following BIPA learning? The population ofthis research was foreign students who study Bahasa Indonesia in IPB. Thedata were collected through questionnaires and observation. BIPA students havepositive motivation to participate in BIPA learning, have a good attitude whenthey are learning, and they hope to be able to teach Indonesian when theyreturn to their home countries. AbstrakBAHASA Indonesia bisa jadi merupakan syarat bagi orang asing yang akan menetap diIndonesia. Untuk itu, Institut Pertanian Bogor (IPB) berusaha untuk memberikanpelayanan ini dengan menawarkan kursus BIPA bagi mahasiswa IPB yang akan belajarpada tingkat S1 dan S2. Namun, para pembelajar yang mengikuti kursus BIPA IPB inilebih didominasi oleh mahasiswa IPB. Mereka selama satu semester ikut kursus inisebelum mereka masuk ke dalam kelas kuliah. Hal ini mengingat pembelajaran di dalamkelas-kelas kuliah lebih banyak menggunakan bahasa Indonesia. Untuk itu, penulisingin menjelaskan apa motivasi mereka untuk mengikuti pembelajaran BIPA IPB?Bagaimana sikap mereka terhadap pembelajaran BIPA IPB? Selanjutnya, apa harapanmereka setelah mengikuti pembelajaran BIPA? Dalam hal ini penulis menggunakan